Corpus planning in Kurdistan Regional Government’s public education from the perspective of supervisors )the case of Erbil( - Saad Abdolrazzaq Qazi (Zanco Journal of Humanity Sciences)
How to deal with the uncertainty of the Kurdish language in Kurdistan's education is the question of this research work. This study sought to discover the importance of planning the language corpus, identifying the weaknesses of corpus planning and their causes. Trying to determine who is responsible for it, the importance of language reform and how it can be done. To this end, four Kurdish education monitors completed questionnaires about the language corpus of Kurdish. The purpose of language corpus is design, grammar, spelling, wordplay and textbook punctuation. The remainder of this article is a theoretical study of the education supervisors, who assisted with this study by examining the specimens and answering the questionnaire. Written surveys were used to collect samples. After that, the table included was compiled, examined and analyzed critically. This article concludes that the development of the Kurdish language program in the Kurdistan region’s education is poor and needs to be revised. This article consists of five parts, which include an introduction, a review of the education supervisor's perspectives, and a thesis on language planning and curriculum development, a sample analysis and conclusion.